Muscle hypertrophy and increased expression of leptin receptors in the musculus triceps brachii of the dominant arm in professional tennis players - Olmedillas, H.; Sanchis-Moysi, J.; Fuentes, T.; Guadalupe-Grau, A.; Ponce-Gonzalez, J. G.; Morales-Alamo, D.; Santana, A.; Dorado, C.; Calbet, J. A. L.; Guerra, B. (European Journal of Applied Physiology, 2010)
In rodents, endurance training increases leptin sensitivity in skeletal muscle; however, little is known about the effects of exercise on the leptin signalling system in human skeletal muscle. Thus, to determine whether chronic muscle loading increases leptin receptor (OB-R170) protein expression, body composition dual-energy X-ray absorptiometry was assessed in nine professional male tennis players (24 ± 4 years old) and muscle biopsies were obtained from the dominant (DTB) and non-dominant (NDTB) arm triceps brachii (TB), and also from the right vastus lateralis (VL). In each biopsy, the protein content of OB-R170, perilipin A, suppressor of cytokine signalling 3 (SOCS3), protein tyrosine phosphatase 1B (PTP1B) and signal transducer and activator of transcription 3 (STAT3) phosphorylation were determined by western blot. The DTB had 15% greater lean mass (P < 0.05) and 62% greater OB-R170 protein expression (P < 0.05) than the NDTB. SOCS3 and PTP1B protein expression was similar in both arms, while STAT3 phosphorylation was reduced in the NDTB. OB-R170 protein content was also higher in DTB than in VL (P < 0.05). In summary, this study shows that the functional isoform of the leptin receptor is up-regulated in the hypertrophied TB. The latter combined with the fact that both SOCS3 and PTP1B protein expression were unaltered is compatible with increased leptin sensitivity in this muscle. Our findings are also consistent with a role of leptin signalling in muscle hypertrophy in healthy humans.